Transmittance Function of Two-ports Nonlinear Fiber Mach-Zehnder Interferometer - Quy, Ho Quang; Tam, Nguyen Thi Thanh; Hoa, Nguyen Van (Communications in Physics, 2012)
In this article a two-ports nonlinear fiber Mach-Zehnder interferometer is proposed. The expression for output-input intensity relation and the transmittance function are derived based on principle operation of optical coupler. The expression of coupling coefficient of coupler is presented. The bell shape of the transmittance function is simulated. The results lead to investigate bistability of two-ports-nonlinear fiber Mach-Zehnder interferometer and to confirm bistable character of it in the future.